Inhibition of invasion and metastasis in choriocarcinoma by migration and invasion inhibitory protein. (December 2022) - Yu, Yan; Peng, Qiaohua; Zhao, Peng; Wang, Lingfang; Weng, Yang; Chen, Xiaojing; Li, Xingxia; Feng, Suwen; Wang, Xinyu; Lu, Weiguo; Xie, Xing; Cheng, Xiaodong
Abstract: Introduction: Choriocarcinoma is a highly invasive gynaecologic malignancy. Molecular mechanism of metastasis in choriocarcinoma is poorly understood. Migration and invasion inhibitory protein (MIIP) regulates cell migration and invasion. Therefore, we aimed to elucidate the function of MIIP in choriocarcinoma. Methods: Choriocarcinoma cell lines, JAR and JEG-3, were transfected with lentivirus carrying the MIIP -interfering RNA (to downregulate MIIP expression) or left untransfected (negative control). Cell migration and invasion were studied using transwell migration assays and scratch assays. In vivo tumour burden was studied using tumour xenograft models in specific-pathogen-free nude mice and live imaging. We elucidated possible molecular signalling pathways using western blotting. Results: In transwell migration and scratch assays MIIP- downregulated JAR and JEG-3 cells migrated and invaded faster compared to their respective negative control cells. Migration and invasion by the MIIP -upregulated SWAN cells was slower than that by negative control SWAN cells. Live imaging revealed that bioluminescence values were higher in MIIP -downregulated tumours than in the negative control tumours. Mice with MIIP -downregulated tumours had higher serum human chorionic gonadotropin (HCG) levels than those with negative control tumours. The MIIP expression was negatively correlated with that of histone deacetylase (HDAC6) and positively correlated with that of acetylated α-tubulin. Discussion: Thus, MIIP —by inhibiting cellular motility in choriocarcinoma—acts as a tumour suppressor gene. This highlights a potential therapeutic target for refractory choriocarcinoma. Additionally, HDAC6 and acetylated α-tubulin may be involved in the regulatory effects of MIIP on the biobehaviour of choriocarcinoma cells. Highlights: MIIP acts as a tumour suppressor gene in choriocarcinoma. MIIP knockdown enhances cancer cell proliferation, invasion and migration ability. MIIP knockdown enhances in vivo metastasis and tumour burden. MIIP expression affects HDAC6 and acetylated α-tubulin expressions.